Physiological performance of nine cacao (Theobroma cacao L.) genotypes under the shadow of three forest species in Santander, Colombia - Agudelo-Castañeda, Genaro Andrés; Cadena-Torres, Jorge; Almanza-Merchán, Pedro José; Pinzón-Sandoval, Elberth Hernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
At present, Colombia has 173,000 ha cultivated with Theobroma cacao, most of which are established in association with fruit or timber trees that provide shade, that can generate income for cocoa growers. In order to select species that make up the agroforestry system, it is necessary to consider the ecophysiological requirements of T. cacao genotypes and the interaction with the agroecological environment, including shade. The objective of this research was to evaluate the physiological performance of nine cocoa clones established in an agroforestry system with Cariniana piryformis, Hevea brasiliensis (Carmen) Cariniana piryformis, and Tectona grandis (Rionegro, Santander province). The photosynthesis rates, transpiration, stomatal conductance and efficient use of water in cocoa clones was monitored in the wet and dry season. The results showed that shade systems influence the photosynthetic rates of cocoa plants. The clones established under the shade system with C. piryformis presented higher rates of photosynthesis (5.39 μmoles CO2 m-2 s-1), both in the wet season and in the dry season. This was attributed to the type of growth and shade provided by this species, which offers better environmental conditions for the physiological performance of cocoa. As a result, this forest species is recommended for shading in the establishment of new areas of T. cacao in the Department of Santander. Individually, the cocoa clones with better echophysiological behavior included TCS19 and TCS13, making their genotypes agronomically important.